ACCOUNTING FRAUD (FRAUD) DETERMINANTS IN THE DISTRIBUTION OF ELEMENTARY SCHOOL OPERATIONAL ASSISTANCE FUNDS IN MEDAN CITY - Rizky br Ritonga; Yenni Samri Juliati Nst (ITB AAS INDONESIA, 2023)
The intent and purpose of this study are to determine the causes of accounting fraud (Fraud) in the distribution of school operational assistance funds (BOS) in the city of Medan. The study's subject is a Medan City elementary school. The type of research used in this study was qualitative descriptive. This study collects data using a questionnaire and uses primary data as a detailed explanation of this research. The principal, treasurer, and secretary were among the 25 people who participated in this study. The occurrence of fraud in the distribution of School Operational Assistance funds in the city of Medan inspired this study. Pressure, opportunity, and rationalization are the independent variables, and School Operational Assistance Fund (BOS) Fraud is the dependent variable. According to the findings of his study, of the three variables, pressure, opportunity, and rationalization, only the rationalization variable has a significant influence on the boss's fraudulent funds. Meanwhile, the variables of pressure and opportunity have little effect on the boss's fraudulent funds.